2013
DOI: 10.2903/j.efsa.2013.3005
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Dietary Reference Values for energy

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) derived dietary reference values for energy, which are provided as average requirements (ARs) of specified age and sex groups. For children and adults, total energy expenditure (TEE) was determined factorially from estimates of resting energy expenditure (REE) plus the energy needed for various levels of physical activity (PAL) associated with sustainable lifestyles in healthy individuals. To account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(79 citation statements)
references
References 198 publications
1
75
0
3
Order By: Relevance
“…Nutrient requirements and references should be differentiated from recommended intakes because of differences in the methodology for their derivation and their intention. Considering amongst other nutrient goals for a given population, reference values are translated into recommendations for managing nutritional risks (EFSA NDA Panel, 2010g NDA Panel, 2010f, 2010d, 2010a, 2012a, 2013b, 2013c, 2013d and endorsed opinions on DRVs for biotin and pantothenic acid for public consultation (EFSA NDA Panel, 2013g, 2013a.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrient requirements and references should be differentiated from recommended intakes because of differences in the methodology for their derivation and their intention. Considering amongst other nutrient goals for a given population, reference values are translated into recommendations for managing nutritional risks (EFSA NDA Panel, 2010g NDA Panel, 2010f, 2010d, 2010a, 2012a, 2013b, 2013c, 2013d and endorsed opinions on DRVs for biotin and pantothenic acid for public consultation (EFSA NDA Panel, 2013g, 2013a.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The Panel decided to extend the methodology chosen in its previous Opinion for deriving ARs for energy for older infants (EFSA NDA Panel, 2013b) to infants from birth to six months. The Panel had based the ARs for older infants on the equation for TEE established by Butte (2005) derived from data from infants exclusively breast-fed for four months and adding energy requirements for growth based on the values proposed by Butte et al (2000) and Butte (2005) and using median body masses from the WHO Growth Standard (WHO Multicentre Growth Reference Study Group, 2006).…”
Section: To < 12 Monthsmentioning
confidence: 99%
See 1 more Smart Citation
“…
the nutritional recommendations, institutions like the WHO and EFSA have moved away from using observed intakes for their guidelines and started using a factorial method [2,3]. We do agree with the statement of Alexy and Hilbig that only a small number of infants were used to determine the energy deposition using doubly labeled water technique.
…”
mentioning
confidence: 55%
“…These are discussed in more detail in the Panel's opinion on DRVs for energy (EFSA NDA Panel, 2013c). In that opinion, the Panel concluded that the equations by Harris and Benedict (1919), Schofield et al (1985), Mifflin et al (1990), Müller et al (2004) and Henry (2005) can be considered as equally valid, but the Panel used, for practical reasons and the comprehensiveness of the underlying database, the equations by Henry (2005) to calculate REE for healthy, normal-weight adults.…”
Section: Proteinmentioning
confidence: 99%